PENGARUH MARKETING MIX TERHADAP MINAT MENGGUNAKAN E-BANKING PADA NASABAH PT BNI CABANG BIREUEN - Hamdani Hamdani (Politeknik Negeri Lhokseumawe, 2018)
Abstract: The porpose of this study is to find the influence of marketing mix consisting of (product,price,place and promotion) that affect the interests of customers using internet banking at PT. Bank Negara Indonesia Branch Bireuen, and see variable which most dominant of that affect the interests of customers using internet banking. Discussion of result of research using multiple regression analysis, the data were processed using SPSS statistical calculation 20. Data collection techniques included interviews and questionnaires. Samples used as many as 100 regular customers BNI Branch Bireuen encountered when conducting a transaction. Analysis tools used are validity and reability test, regression analysis, and classical assumption. The result showed that varibles Product (X1), Price (X2), Place (X3), and Promotion (X4) simultaneously have a significant effect on the interests of customers using internet banking (Y) with sig F smaller than α (0,05). The result also showed that the product variable (X1) is the most dominant variable that influence the interests of customers using internet banking(Y) which is indicated by highest beta coefficient is 0.577 and the value of the greatest Thitung is 5.535. Keywords: Product, Price, Place, Promotion, The Interests of Customers